The Evolution of AI Characters in Children’s Literature: A Societal Perspective - Rachel Hamilton; Christopher Piper (Leaf Journal, 2025)
This article explores how AI characters in children's literature are evolving from the traditional ‘Pinocchio paradigm’, where artificial beings strive to become human or gain human approval, toward more autonomous identities. With a focus on Mary Pearson’s The Adoration of Jenna Fox, Peter Brown’s The Wild Robot, and Kirsty Applebaum’s TrooFriend, it analyses narrative techniques used to help AI characters assert these distinct identities. Drawing on Hayles' (1999) posthumanist theory, which challenges the assumption that consciousness and identity must be rooted in biological humanity, this article argues that, while progress has begun, AI characters in these texts remain constrained by the anthropocentric framing that has been challenged more successfully in other media. It proposes an evaluative framework for AI representation, inspired by the Bechdel test, to encourage authors to depict AI characters on their own terms.